The Role of Leadership on Sustainable Improvement in Improving Product Quality in the Division of PT. North Sumatra Coal Inalum - Kholilul Kholik; Iman Sudirman; Yusuf Arifin (Universitas Muhammadiyah Palu, 2022)
Leaders in organizations including company managers who have a goal to increase production and efficiency in order to maximize results for the organization they lead. A leader must be able to bring the organization or company and all its employees with a clear vision. Only with a clear vision, concepts and organizational goals can be described properly, but leaders must also be able to mobilize all resources within the company to move together and work together to achieve goals effectively. Leaders must have a clear vision in building and developing a business, especially those related to product quality improvement. A clear vision and mission of the company and implemented together is the key to the company's success to compete in the business world, such as PT. Inalum Coal North Sumatra which produces quality products and is able to compete in the world. The objectives of this study are 1) to determine the role of leadership in continuous improvement and its implications for the quality of the product division of PT. North Sumatra Coal Inalum; 2) to determine the factors that affect the improvement of product quality in the Division of PT. North Sumatra Coal Inalum. This research is a case study which was analyzed with a qualitative approach. This research shows that the role of leadership is very large in making continuous improvements so as to produce quality products that can compete in the business world on a national and international scale.